Low Testosterone at First PSA Failure and Assessment of the Risk of Death in Men with Unfavorable-Risk Prostate Cancer Treated on Prospective Clinical Trials - Atkins, Katelyn M. (Cancer, 2017)
BACKGROUND: Low testosterone at prostate cancer (PC) diagnosis has been associated with a worse prognosis. Whether this is true and how to define the best treatment approach at first PSA failure has not been elucidated and was studied. METHODS: Between 1995–2001, 58 men with unfavorable-risk PC treated on clinical trials with radiation and androgen deprivation therapy (ADT) had testosterone levels at PSA failure available. Cox and Fine and Gray regressions were performed to ascertain whether low versus normal testosterone was associated with the risk of PC-specific, other-cause and all-cause mortality (PCSM, OCM, ACM) adjusting for age, salvage ADT and known PC prognostic factors. RESULTS: After a median follow-up of 6.68 years following PSA failure, 31 men (53.4%) died; 10 from PC (32.3%), of which 8/11 (72.7%) versus 2/47 (4.3%) occurred in men with low versus normal testosterone at PSA failure, respectively. A significant increase in the risk of ACM (adjusted hazard ratio, AHR[2.54, 95%CI 1.04–6.21]; P=0.04) and PCSM (AHR[13.71, 95%CI 2.4–78.16]; P=0.003), with a reciprocal trend toward decreased risk of OCM (AHR[0.18, 95%CI 0.02–1.55]; P=0.12) was observed in men with low versus normal testosterone. CONCLUSION: Low, but not necessarily castrate, testosterone levels at PSA failure confers a very poor prognosis. These observations provide evidence to support testosterone testing at PSA failure. Given prolonged survival when abiraterone or docetaxel is added to ADT in men with castrate-sensitive metastatic PC and possibly localized high-risk PC provides rationale supporting their use with ADT in men with low testosterone in the setting of a phase II trial.